Guillain–Barre syndrome: An atypical presentation of IRIS on initiation of antiretroviral therapy in a newly diagnosed HIV infected - Hardik Patel; Debajyoti Majumdar; Dolanchampa Modak (Journal of Clinical and Scientific Research)
We report the occurrence of Guillain–Barre syndrome (GBS) along with disseminated histoplasmosis in a 45-year-old male who had tested seropositive for human immunodeficiency virus (HIV). Histoplasmosis was treated with conventional amphotericin B followed by oral itraconazole. Co-trimoxazole prophylaxis and antiretroviral drugs were initiated, as per the National AIDS Control Organization (NACO) recommendations, and the patient was discharged in a stable condition. After 3 months of treatment, he was readmitted with rapid onset of bilateral weakness of limbs, initially lower and then progressed to upper limbs along with difficulty in swallowing. On evaluation, he had symmetrical quadriparesis in the form of motor weakness, loss of posterior column sense, bulbar involvement and bilateral facial lower motor neuron nerve palsy with areflexia. Elevated protein was detected in cerebrospinal fluid. Diagnosis of GBS was made, patient was treated with intravenous immunoglobulin and invasive ventilatory support was added for respiratory paralysis. He showed clinical signs of improvement and was discharged in a favourable condition after 2 weeks. At the time of discharge, his CD4+ T-cell count was 586,000 cells/mm3 and plasma viral load was <150 copies/mL.